Non Muslim consumers intention to purchase halal product in Malaysia : Proposed framework - Saleh, Hasan; Rajandran, Thurga (Redfame Publishing, 2024)
This study explores the factors influencing non-Muslim consumers' intentions to purchase halal products, amidst a diverse demographic landscape. The study identifies key elements such as halal awareness, certification, marketing strategies, and knowledge that significantly impact purchasing decisions. Findings reveal that halal certification is the most influential factor, enhancing consumer trust and confidence in halal products. Additionally, effective marketing and increased awareness about halal concepts are crucial in shaping non-Muslim consumers' attitudes. The study aims to bridge the knowledge gap regarding halal practices among non-Muslims, fostering greater acceptance and promoting ethical consumption. Insights from this study are expected to inform businesses on how to tailor their strategies to effectively engage non-Muslim consumers in the growing halal market.